Design and Construction of a Blood Type Detection Device with a Color Sensor Based on Arduino Uno - Ilham Qomaruzzaman; Wisnu Adi Prasetyanto; Bayu Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2025)
A Blood Type Detector is an electronic device used to detect human blood types. Blood type detection and observation are generally carried out through a series of experiments on blood samples, namely antiserum reactions (anti-A, B, AB, and D). Currently, determining a person's blood type is still done manually. This will certainly be complicated and require extra attention if the blood sample to be tested is quite large in number, it will take a lot of time and is inefficient. The purpose of research on a Blood Type Detector Tool with an Arduino Uno-Based Color Sensor is to improve the efficiency, accessibility, and quality of health care as a whole. As well as ease of access and data processing for users. This tool is designed using a Color Sensor so that it can detect the occurrence of agglutination or non-agglutination reactions from blood samples that have been mixed with antigens. The working system settings of this tool are based on Arduino Uno, the results of which will be displayed on the LCD, then a sound will appear from the results of the blood type being read. In the blood type test function test process, a blood sample and antigen are required, where the blood sample and antigen are mixed together, the ratio is one drop of blood with one drop of antisera, then stirred together, so that agglutination or non-agglutination occurs in the blood sample that has been mixed with the antigen. After sampling, the blood type tester will detect the four blood samples dropped onto the sample card. When the blood sample in anti-A and AB coagulates, the sensor will read a value of >200 for blood type A.